Anthelmintic effect of biorationals against the root knot nematode, Meloidogyne incognita colonizing chilli rhizosphere - Karunasena, P.D.N.S.; Pakeerathan, K.; Thileepan, T.; Mikunthan, G. (Sabaragamuwa University of Sri Lanka, 2022)
Chilli is an important cash crop of Sri Lanka (Capsicum annum). A variety of biotic-abiotic stresses impair the chilli production particularly in high potential chilli producing areas in dry and intermediate zones of Sri Lanka. Multiple cropping and continuous cultivation of the same crop on the same plot of land increases the problem of soil-borne diseases, specially plant parasitic nematodes (Dhillon et al., 2019). Root-knot nematode causes damage on a variety of crops, including chillies, tomatoes, and potatoes. The Root-knot nematode (Meloidogyne spp.) belongs to the family Meloidogynidae is the primary nematode species infesting chili plants. They pierce the root and enter the vascular system, where they cause metabolic changes that contribute to gall formation (Thiyagarajan, 2014).